2019
DOI: 10.3390/en12142766
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Optimal Design and Control of Fourth Generation District Heating Networks with Thermal Energy Storage

Abstract: In the quest to increase the share of renewable and residual energy sources in our energy system, and to reduce its greenhouse gas emissions, district heating networks and seasonal thermal energy storage have the potential to play a key role. Different studies prove the techno-economic potential of these technologies but, due to the added complexity, it is challenging to design and control such systems. This paper describes an integrated optimal design and control algorithm, which is applied to the design of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The case study showed that ADMM algorithm had the faster convergence speed than particle swarm optimization (PSO). van der Heijde et al [30] developed a two-stage optimization algorithm to achieve the optimal design and dispatching of integrated heating system. The genetic algorithm (GA) was adopted to realize the equipment capacity configuration in the first layer, and the optimization solution toolbox of Python was used to achieve the optimal dispatching of the equipment in the second layer.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The case study showed that ADMM algorithm had the faster convergence speed than particle swarm optimization (PSO). van der Heijde et al [30] developed a two-stage optimization algorithm to achieve the optimal design and dispatching of integrated heating system. The genetic algorithm (GA) was adopted to realize the equipment capacity configuration in the first layer, and the optimization solution toolbox of Python was used to achieve the optimal dispatching of the equipment in the second layer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the two following constraints could be used to ensure the reliability of switching: First, the configuration capacity of CCP is increased to provide sufficient power for the IT equipment and chillers during the pre-cooling including IT, chiller, etc. Equations (30) and (31) can be brought into the configuration model as a constraint to avoid switching faults. Clearly, the above switching logic is based on the fact that the chillers can meet the total cooling load solely.…”
Section: Switching Logic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Section 3.3) deal with this subject. Since 2016, there have always been at least six articles on this topic, including the last nine in 2019: [46][47][48][49][50][51][52][53][54]. Furthermore, the top five of the most relevant journals increasingly deal with district heating in studies on MESP: most frequent subject in Energy Policy and Applied Energy and second most frequent subject in Energy as well as Energies (cf.…”
Section: District Heatingmentioning
confidence: 99%